2016
DOI: 10.1111/aab.12317
|View full text |Cite
|
Sign up to set email alerts
|

Humic acid differentially improves nitrate kinetics under low- and high-affinity systems and alters the expression of plasma membrane H+-ATPases and nitrate transporters in rice

Abstract: Humic acids (HAs) have a major effect on nutrient uptake, metabolism, growth and development in plants. Here, we evaluated the effect of HA pretreatment applied with a nutrient solution on the uptake kinetics of nitrate nitrogen (N-NO 3 − ) and the metabolism of nitrogen (N) in rice under conditions of high and low NO 3 − supply. In addition, the kinetic parameters of NO 3 − uptake, N metabolites, and nitrate transporters (NRTs) and the plasma membrane (PM) H + -ATPase gene expression were examined. The plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 69 publications
2
24
0
2
Order By: Relevance
“…In their study Ertani et al (2011) demonstrated that lignosulphonates treatment improved N assimilation in maize plants through the stimulation of key enzymes (glutamate-synthase and glutamine-synthetase) and also by promoting photosynthetic activity through the stimulation of both rubisco enzyme activity as well as chlorophyll biosynthesis. Besides the biostimulant-mediated enhancement of root growth, vegetal-based biopolymers can also upregulate the expression of genes encoding for plasma membrane H + -ATPases and nitrate transporters, resulting in greater efficiency in nitrate uptake and assimilation ( Tavares et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In their study Ertani et al (2011) demonstrated that lignosulphonates treatment improved N assimilation in maize plants through the stimulation of key enzymes (glutamate-synthase and glutamine-synthetase) and also by promoting photosynthetic activity through the stimulation of both rubisco enzyme activity as well as chlorophyll biosynthesis. Besides the biostimulant-mediated enhancement of root growth, vegetal-based biopolymers can also upregulate the expression of genes encoding for plasma membrane H + -ATPases and nitrate transporters, resulting in greater efficiency in nitrate uptake and assimilation ( Tavares et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…There was a decline in Ca uptake efficiency with the increase in C-HA concentration. The HS are able to optimize nutrient acquisition by plants, whether by stimulation of cell transporters that increase P uptake (JINDO et al, 2016), or stimulation of plasmatic membrane H + -ATPase, generating an electrochemical difference of protons between it and the outside medium which increases nutrient uptake (CANELLAS et al, 2015), including N acquisition by plants (TAVARES et al, 2017). HS acts stimulating the number of physiologically active roots (RIMA et al, 2011) and increase root growth (MELO et al, 2015;ROSE et al, 2014), Such effects depends on the HA concentration and properties (AGUIAR et al, 2009).…”
Section: Efficiency Of Nutrient Uptakementioning
confidence: 99%
“…According to Pinheiro et al (2010), increase in HA concentration in nutrient solution drastically reduced accumulation of Fe, Cu, and Zn; however, for Mn, this effect was not so pronounced as for Fe, Cu, Zn and B; depending on the source, Mn accumulation improves when the concentration of 10 mg L -1 C-HA is used. Application of HA increasing macronutrient accumulation in plants is shown in greater magnitude for N, P, K, and Ca (AZCONA et al, 2011;EKINCI et al, 2015;MELO et al 2015;TAVARES et al, 2017), whereas, for S and Mg, this effect may be small or null (AZCONA et al, 2011;PINHEIRO et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Outra contribuição importante dos MPVC para a nutrição radicular é a estimulação de enzimas como as H + -ATPases da membrana plasmática, que convertem a energia livre liberada pela hidrólise do ATP em um potencial eletroquímico trans-membranar usado para a importação de nitrato e outros nutrientes (Du Jardin, 2015). Além da captação de nutrientes, o bombeamento de prótons pelas ATPases da membrana plasmática também contribui para o afrouxamento da parede celular e o aumento celular levando a maiores rendimentos por parte da planta (Zandonadi et al, 2010(Zandonadi et al, , 2016Tavares et al, 2017).…”
Section: Introductionunclassified